Plant ultrasound detection: a cost-effective method for identifying plant ultrasonic emissions - Luca Bonisoli; Ivano Pelicella; Laura Arru (Plant Signaling & Behavior)
Plants have been observed to produce short ultrasonic emissions (UEs), and current research is focusing on developing noninvasive techniques for recording and analyzing these emissions. A standardized methodology has not been established yet; in this paper we suggest a cost-effective procedure for recording, extracting, and identifying plant UEs using only a single ultrasound microphone, a laptop computer, and open-source software.